The physiological responses to running after cycling in elite junior and senior triathletes - Millet, G. P.; Bentley, D. J. (International Journal of Sports Medicine, 2004)
The purpose of this investigation was to compare the physiological responses in cycling and the energy cost (EC) of running after cycling in elite junior (Jmale and Jfemale) and senior (Smale and Sfemale) triathletes and to determine the relationship between laboratory physiological parameters and performance in an elite "standard" distance triathlon. Thirty-one elite triathletes competing at World Championship level (age: 23.4 ± 4.8 y; height: 172.6 ± 6.8 cm; body mass: 64.4 ± 7.2 kg; V·O2max = 67.8 ± 8.3 ml × kg-1 × min-1) comprising Jmale (n = 7), Jfemale (n = 6), Smale (n = 9) and Sfemale (n = 9) athletes performed a laboratory trial that consisted of submaximal treadmill running (to determine EC), maximal then submaximal cycle ergometry (to determine the peak power output [PPO], V·O2max, the ventilation threshold [VT] and cycling economy) followed by an additional submaximal running bout. Swimming, cycling, running and overall race performance (min) over a standard event was also measured in the field. Smale had a faster cycle, run and overall triathlon times than Jmale. Sfemale demonstrated a faster cycle and overall triathlon time than Jfemale. The V·O2max (74.7 ± 5.7 vs. 74.3 ± 4.4 and 60.1 ± 1.8 vs. 61.0 ± 5.0 ml × kg-1 × min-1) and cycling economy (72.5 ± 4.5 vs. 73.8 ± 4.3 and 75.6 ± 4.5 vs. 79.8 ± 9.8 W × l-1 × min-1) were similar between the junior and senior, in both male and female triathletes. However, Sfemale possessed a significantly higher PPO than Jfemale. Smale had a higher VT (%V·O2max) than Jmale whereas the VT was similar in Jfemale and Sfemale. There were no significant differences in EC change from the first to the second running bout between Jmale and Smale, whereas, in contrast, Jfemale exhibited a significantly (p < 0.05) higher difference in EC than Sfemale. When all subjects were pooled, the overall triathlon time (min) was significantly correlated to V·O2max (r = -0.80; p < 0.001) and PPO (W) (r = -0.85; p < 0.001) in cycle ergometry. In conclusion, elite senior triathletes can be distinguished from their younger (junior) counterparts, mainly by a higher PPO in cycling and a lower increase in the whole body energy cost of running after cycling in female and by a higher ventilatory threshold in male triathletes.